2012
DOI: 10.3762/bjoc.8.207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a chiral cubane-based Schiff base ligand in asymmetric catalysis reactions

Abstract: SummaryRecently, a novel chiral cubane-based Schiff base ligand was reported to yield modest enantioselectivity in the Henry reaction. To further explore the utility of this ligand in other asymmetric organic transformations, we evaluated its stereoselectivity in cyclopropanation and Michael addition reactions. Although there was no increase in stereocontrol, upon computational evaluation using both M06L and B3LYP calculations, it was revealed that a pseudo six-membered ring exists, through H-bonding of a cuby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Some of the oxa-cage systems play an important role in molecular recognition and inclusion phenomena (Marchand et al, 1998). Cage hydrocarbons are useful as core frameworks for photonic/electronic materials (Giacalone & Martín, 2006;Lebedeva et al, 2015) and ligands for organocatalysis (Biegasiewicz et al, 2012).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Some of the oxa-cage systems play an important role in molecular recognition and inclusion phenomena (Marchand et al, 1998). Cage hydrocarbons are useful as core frameworks for photonic/electronic materials (Giacalone & Martín, 2006;Lebedeva et al, 2015) and ligands for organocatalysis (Biegasiewicz et al, 2012).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…186 Computational work showed that the poor stereoselectivity is derived from the absence of any steric hindrance on the metal center. Evidence of cubyl hydrogen interaction with the metal center decreases the dihedral angle of the chiral trans-1,2-diaminocyclohexane ring ( Figure 20 and Scheme 64).…”
Section: Cubyl Chiral Ligandmentioning
confidence: 99%
“…Evidence of cubyl hydrogen interaction with the metal center decreases the dihedral angle of the chiral trans-1,2-diaminocyclohexane ring ( Figure 20 and Scheme 64). 186 …”
Section: Cubyl Chiral Ligandmentioning
confidence: 99%
“…Structure of imidazole and imidazole N-oxides, 78 cubanebased Schiff base ligands, 79 and paracyclophanyl imine 80 for asymmetric cyclopropanation reactions Recently, a novel chiral cubane-based Schiff base ligand ( Figure 12) was tested in the cyclopropanation reaction, but with little success (moderate conversion, very low enantiomeric excesses, and moderate or no diastereoselectivity). Using both M06L and B3LYP calculations, the most stable conformation was found to have a pseudo sixmembered ring, through hydrogen bonding of one cubyl hydrogen to the copper core.…”
Section: Figure 12mentioning
confidence: 99%